Analisis Groundwater Study Using Vertical Electrical Sounding (VES) Data Based on Resistivity and Porosity of Rocks in Kampung Melayu, Bengkulu City - Tella Dwi Syaputri; Suhendra Suhendra; Halauddin Halauddin; Liza Lidiawati; Risma Nurhidayah (Jurnal Ilmiah Sains, 2024)
This research aims to identify groundwater based on the value of resistivity and porosity of rocks, which are important parameters in the management of groundwater resources and Development Planning in the region. This groundwater research using Vertical Electrical Sounding (VES) data based on the value of resistivity and porosity of rocks was carried out by measuring resistivity using the (VES) method at 20 sounding points located in Kampung Melayu District, Bengkulu City. The VES method is one of the approaches in the geoelectric method to determine the lithological characteristics of subsurface rocks. Resistivity Data obtained were then inverted and analyzed and interpreted to obtain lithology of subsurface rocks and groundwater level distribution in Kampung Melayu, Bengkulu City. The results showed the presence of groundwater based on low resistivity anomaly values with a range of values from 5 to 30 meters in the West and 10 to 50 meters in the East, with resistivity values ranging between 5 Ω.m up to 45 Ω.m. This research is expected to make a significant contribution to the management of groundwater resources in the District of Kampung Melayu, Bengkulu City and can be the basis for development planning in the area. In addition, it is hoped that the results of this research can be a reference for further research in the field of hydrogeology and groundwater modeling. Keywords: Aquifer; geoelectricity; groundwater; porosity; resistivity